Gap year : how delaying college changes people in ways the world needs - O'Shea, Joseph, 1986- (John Hopkins University Press, 2013)
The idea of the gap year has taken hold in America. Since its development in Britain nearly fifty years ago, taking time off between secondary school and college has allowed students the opportunity to travel, develop crucial life skills, and grow up, all while doing volunteer work in much-needed parts of the developing world.